CASE REPORT: CONJUNCTIVITIS IN PUG - Putra, Gede Herdian Permana; Suartha, I Nyoman; Erawan, I Gusti Made Krisna (Buletin Veteriner Udayana; Vol. 14 No. 1 February 2022, 2022)
Conjunctivitis is inflammation of the conjunctiva. The case of a dog named Ve is the breed Pug dogs 10 months of age, having an eye disorder. Ve has conjunctivitis in the eye of the dexter and sinister part. Ve was reported to have conjunctivitis at 3 months of age. Based on the results of the physical examination of the red eye mucosa, in the eyes sinister the eyeball is not visible (atrophy), which is accompanied by mucopurulent exudate discharge, the part eye dexter eyes looks cloudy, accompanied by mucopurulent exudate and hyperpigmentation of the skin due to Demodex sp . Based on identification and examination, conjunctivitis suffered Ve is caused by trauma accompanied by secondary bacterial infection. From the results of routine hematology examination, it shows lymphocytosis, eosinophilia and thrombocytopenia. Eye therapy was given in the form of Erlamycetin® eye ointment antibiotics and Calvidog® vitamin, while the skin was given dipenhidramine HCl injection and invermectin injection.